Analisis Ketepatan Pemberian Opini Akuntan Publik di Indonesia - Lukmanul Hakim Rusdi; Yuliansyah Yuliansyah; Rindu Rika Gamayuni (Penerbit Goodwood, 2023)
Purpose: This study aims to explain the problem of the accuracy of giving opinions given by public accountants in Indonesia, using framing theory analysis. In this study we developed an analysis of the accuracy of opinions in which we observed matters that were the causes of non-compliance by public accountants, so as to be able to provide more complex and in-depth information to understand attitudes, perceptions, emotions, beliefs about the motives and behavior of informants. Methodology: The informants for this study were 12 Public Accountants who had permission from the Ministry of Finance of the Republic of Indonesia to sign the Independent Auditor's Report. Data collection techniques were using semi-structured interviews, testing the validity of the data using the triangulation method and analyzing and processing data using Nvivo software version 12. Results: The results of the study show that the accuracy of giving a Public Accountant's opinion is influenced by: Auditor, Client Integrity, Public Accountant Integrity and Audit Planning. The violation committed by the Public Accountant is giving an opinion that is not in accordance with the actual situation, due to: not complying with Standard Auditing (SA) 230 regarding Audit Documentation, not complying with SA 500 Audit Evidence, providing audit services not through KAP, providing audit services but the license has been revoked, audit reports are not supported by working papers, receive audit assignments that are being audited by another KAP, have not complied with SA 510 Initial Balances, have not implemented Quality Control Standards, have not fully reported audit clients, and have not maintained working papers. Limitations: This study examines the existence of Framing Theory, Auditing understanding, and the problems of the practice of the Public Accountant Profession regarding the implementation of Professional Ethics and Laws. To provide input to the practice of Public Accountants that in carrying out practices must be in accordance with Auditing Standards and applicable rules.